2023
DOI: 10.1002/advs.202303711
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Gly2019Ser Mutation Promotes ER Stress via Interacting with THBS1/TGF‐β1 in Parkinson's Disease

Longping Yao,
Fengfei Lu,
Sumeyye Koc
et al.

Abstract: The gene mutations of LRRK2, which encodes leucine‐rich repeat kinase 2 (LRRK2), are associated with one of the most prevalent monogenic forms of Parkinson's disease (PD). However, the potential effectors of the Gly2019Ser (G2019S) mutation remain unknown. In this study, the authors investigate the effects of LRRK2 G2019S on endoplasmic reticulum (ER) stress in induced pluripotent stem cell (iPSC)‐induced dopamine neurons and explore potential therapeutic targets in mice model. These findings demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…We also investigated the pathological changes in the placenta of each group because of the commonly admitted pertinence to PE and defective placental function. It has been reported that THBS1 could directly bind to transforming growth factor‐β1 (TGF‐β1), [ 31 ] and it could regulate collagen formation and induce tissue fibrosis through interaction with TGF‐β1). [ 32 ] Therefore, Masson staining was used to detect whether THBS1 caused the side effect of placental fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…We also investigated the pathological changes in the placenta of each group because of the commonly admitted pertinence to PE and defective placental function. It has been reported that THBS1 could directly bind to transforming growth factor‐β1 (TGF‐β1), [ 31 ] and it could regulate collagen formation and induce tissue fibrosis through interaction with TGF‐β1). [ 32 ] Therefore, Masson staining was used to detect whether THBS1 caused the side effect of placental fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…We managed to identify transcripts of THBS1 , which was noted to be involved in multiple investigated immune-related pathways, namely angiogenesis, phagocytosis, apoptosis, and chronic inflammation. Previous studies have reported an association between the upregulation of THBS1 and increasing neuroinflammation, which put the CNS in jeopardy (Wang et al, 2023 ; Yao et al, 2023 ). This suggests the upregulation observed in the AD cohort implied an increasing inflammatory response that fits with precedent postulations.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD) is a progressive neurological disorder characterized by tremor, rigidity, and bradykinesia associated with progressive neuronal loss in the substantia nigra and other brain structures [ 1 ]. Although Parkinson's disease is primarily considered a disease that produces motor symptoms, it frequently manifests non-motor symptoms such as dementia and autonomic deficits in patients with it [ [2] , [3] , [4] ]. Symptomatic treatment of PD involves dopamine medications like levodopa, while surgical treatment is sometimes performed in more severe cases.…”
Section: Introductionmentioning
confidence: 99%